The Influence Of Transformational Leadership, Psychological Well-Being, And Work Stress On The Work Ethic Of Elementary School Teachers - Lia Maulia; Sutarto Hadi; Sulistiyana Sulistiyana (Universitas Negeri Malang, 2026)
Abstract: This study aims to analyze the effects of transformational leadership, psychological well-being, and job stress on the work ethic of elementary school teachers. Teachers’ work ethic plays a crucial role in improving the quality of basic education, particularly in semi-rural areas characterized by limited resources and complex work dynamics. This research employed a quantitative approach using a path analysis design. The research population consisted of all elementary school teachers in Bungur District, Tapin Regency, with a total sample of 101 teachers selected through a total sampling technique. Data were collected using standardized Likert-scale questionnaires that had been tested for validity and reliability. Descriptive and inferential analyses were conducted to examine both direct and indirect relationships among variables. The results indicate that transformational leadership, psychological well-being, and job stress simultaneously have a significant effect on teachers’ work ethic. Partially, psychological well-being was found to be the most dominant factor in enhancing teachers’ work ethic, while job stress had a significant negative effect. Furthermore, transformational leadership not only exerts a direct influence on teachers’ work ethic but also indirectly strengthens it through the improvement of teachers’ psychological well-being. In conclusion, the findings emphasize that strengthening teachers’ work ethic is more effectively achieved through a humanistic leadership approach that prioritizes psychological well-being, rather than relying solely on strategies aimed at reducing work-related stress. Keywords: transformational leadership; psychological well-being; work stress; teachers’ work ethic